2012
DOI: 10.1073/pnas.1115674109
|View full text |Cite
|
Sign up to set email alerts
|

Buckling-induced encapsulation of structured elastic shells under pressure

Abstract: We introduce a class of continuum shell structures, the Buckliball, which undergoes a structural transformation induced by buckling under pressure loading. The geometry of the Buckliball comprises a spherical shell patterned with a regular array of circular voids. In order for the pattern transformation to be induced by buckling, the possible number and arrangement of these voids are found to be restricted to five specific configurations. Below a critical internal pressure, the narrow ligaments between the voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(181 citation statements)
references
References 32 publications
(33 reference statements)
2
171
0
Order By: Relevance
“…[12][13][14] An emerging opportunity in the engineering of soft machines is to harness these instabilities to achieve new functionalities. [15][16][17] For example, buckling has proven useful in the design of stretchable soft electronics, [18,19] tunable materials, [20][21][22][23] and fluidic actuators. [24] We have previously demonstrated that reversible buckling of elastomeric beams can be used to make a torsional soft actuator.…”
mentioning
confidence: 99%
“…[12][13][14] An emerging opportunity in the engineering of soft machines is to harness these instabilities to achieve new functionalities. [15][16][17] For example, buckling has proven useful in the design of stretchable soft electronics, [18,19] tunable materials, [20][21][22][23] and fluidic actuators. [24] We have previously demonstrated that reversible buckling of elastomeric beams can be used to make a torsional soft actuator.…”
mentioning
confidence: 99%
“…We derived the designs of the structures that we fabricated and tested empirically, but they are conceptually related to shape-changing solids. [18][19][20]23] Future demonstrations will apply the design rules established in these related structures to optimize and expand the varieties of motions achievable by soft structures. Further, the advantages this approach offers to the fabrication of topologically complex (in terms of mechanical and physical properties) structures will provide routes to new shape-changing structures with additional functionalities (e.g., electrical conductivity) that were previously inaccessible.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] This control is achieved by designing structures with mechanical instabilities that buckle in a predictable way when subjected to mechanical deformation (e.g., compression). [18][19][20]23] Following this approach it is possible to produce structures that undergo large (>50%), isotropic volume changes, and that have negative…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structures have also been created through the use of three-dimensional (3D) printing technology, where engineered mechanical instabilities produce folding behaviors as the object is compressed [8]. Using origami-like patterns and the self-folding behavior of knits, textiles exhibiting auxetic behavior have been developed [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%